Curricular reform in Slovakia regarding the attitudes of basic school teachers - Štefan Porubský; Marian Trnka; Vladimír Poliach; Radka Cachovanová (Czech Pedagogical Society, 2016)
In 2008, a curricular reform was begun in Slovakia. It focused on introducing a two-level model of curriculum at pre-primary, primary and secondary schools. The reform has been met with mixed reactions from teachers and school administration staff. Our paper provides brief information on the nature of this reform,  the content of the reform curricular documents and some of the results of a questionnaire survey regarding the attitudes of teachers in basic schools (primary and lower secondary level of education) towards the reform. Their ratings are examined in three areas: satisfaction with the development of the Slovak school system in the last six years, the importance of curricular changes and the effect of these changes.